Konseling Behavior dalam Meningkatkan Manajemen Diri Siswa Remaja - Kholijah, Siti; Ridjal, Tadjoer; Habsy, Bakhrudin All (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2019)
Self management is the process of specific steps consisting of planning, organizing, mobilizing and controlling needed to achieve the expected goals, so that individuals can do better. The design of this study was purposive sampling pretest-posttest control group design, which was analyzed using the T-Test. The population in this study were VIII grade students of Budi Utomo Perak Jombang Middle School with 49 students. The sample of this study was 6 students who were divided into experimental groups and control groups. The instruments in this study are self-management questionnaires. Based on the data analysis the results of the tcount are r 0.985 and the probability value (Sig. (2-tailed) is 0.381 with df = 4. Then the value is compared with the price of ttable at a significant level of 5% two-party test with df = 4 2,776. thitung .985 is greater than t_table 2.776 and the probability value is 0.381, it can be accounted for student management before and approved counseling of Middle School students.Of this study can be conveyed suggestions: (1) Teacher Guidance and Counseling, counseling behavior can be applied to improve student self-management Middle School and for the next researcher can use the use and other relevant techniques used that are used by researchers now